The influence of Capital Adequacy Ratio, Third-Party Funds, Operating Cost to Operating Income Ratio, Loan-to-Deposit Ratio, Non-Performing Loans, and fintech adoption on bank performance - Apriani Simatupang; Veny Anindya Puspitasari (Cita konsultindo, 2024)
This paper investigates the impact of Capital Adequacy Ratio (CAR), Third Party Funds, Operating Expenses to Operating Income Ratio, Loan-to-Deposit Ratio (LDR), Non-Performing Loans (NPL), and fintech adoption on bank performance, of banks in Indonesia across 107 banks grouped into 4 KBMI categories. The data period for our study is from October 2021 to March 2022. The performance of banks in this paper is measured by ROA (Return on Assets) and NIM (Net Interest Margin). We employ regression analysis for our study. Our main findings are as follows. First, we found that CAR, Third Party Funds, Operating Expenses to Operating Income Ratio, LDR, NPL, significantly influence ROA, while fintech adoption does not significantly affect ROA. Second, we found that CAR, Third Party Funds, NPL, and Operating Expenses to Operating Income Ratio significantly influence NIM, whereas the adoption of DPK and fintech does not significantly affect NIM. Finally, our control variables indicate that inflation significantly influences ROA, while inflation towards NIM and growth towards ROA and NIM do not significantly affect them.